Adolescent mothers' lived experiences whilst providing continuous kangaroo mother care: A qualitative study - Anneline E. Robertson; Talitha Crowley (AOSIS, 2020)
Background: Kangaroo mother care (KMC) is the practice of skin-to-skin contact between an infant and parent and has been found to improve the growth and decrease the morbidity and mortality of low-birth-weight and premature infants. Adolescent pregnancy is associated with a preterm birth or low-birth-weight infant; therefore, it is possible that an adolescent mother may have to provide KMC. The adolescent mother, who is likely to have her first experience of motherhood, may have to be supported to ensure that she is able to provide KMC and the routine care for her preterm infant. The literature review did not reveal any research conducted in the Western Cape province on the experiences of adolescent mothers whilst providing KMC. It is, therefore, important to conduct research on this phenomenon so that the lived experiences of adolescent mothers whilst providing KMC can be described. Aim: The aim of this study was to explore the lived experiences of adolescent mothers whilst providing continuous KMC. Setting: The study was conducted in a district and central hospital KMC wards in Cape Town in the Western Cape province of South Africa. Methods: A qualitative, descriptive, phenomenological research design was used. Ten adolescent mothers were selected through purposive sampling. Semi-structured in-depth interviews were conducted, transcribed and analysed using Colaizzi's framework. Results: Three themes emerged from the data: providing KMC, the interactions and the support received. Conclusion: Supportive educative environments should be established in the KMC wards to ensure that the adolescent mothers receive holistic support.